Characterization of the complete mitochondrial genome of Sphaeramia orbicularis (Kurtiformes, Apogonidae). Issue 1 (2nd January 2019) - Song, Ha Yeun; Hwang, Hyun-Ju; Jo, Seonmi; Jung, Seung-Hyun; Kim, Yu Cheol; Yoo, Jong Su
Abstract: The complete mitochondrial genome was determined for the orbicular cardinalfish Sphaeramia orbicularis belonging to the family Apogonidae. The length of the complete mitochondrial genome is 16, 458 bp and has the typical vertebrate mitochondrial gene arrangement, consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. Phylogenetic analysis using mitochondrial genomes of 9 species showed that S. orbicularis formed a well-supported monophyletic group with other Apogonidae species.